Foodservice Management - Payne-Palacio, June; Theis, Monica (Singapore : Pearson, 2005)
"Introduction to Foodservice, Tenth Edition is a practice-based textbook designed specifically for students studying foodservice management in four-year degree programs or technical colleges. The material is appropriate for higher education programs in dietetics, foodservice administration, and hospitality management. The text includes the essential information to understand and manage any type of foodservice operation in both the commercial and noncommercial sectors of the foodservice industry. The book is organized into five parts. Part 1 provides an informative, historical overview of the foodservice industry and a review of foodservice as a system. Part 2 presents the fundamentals of foodservice that form the foundation of any operation. Included are chapters on food safety and menu planning. Part 3 serves as the heart of the text by providing a description of each functional operation of a foodservice operation in relation to the systems model. Part 4 emphasizes the physical plant and covers facility design, equipment, and environmental management. The book concludes with Part 5, which is a presentation of the linking processes used to manage foodservice operations. Included here are chapters on leadership, performance improvement, and marketing."
Part 1. The foundations -- Part 2. The fundamentals -- Part 3. The operational functions -- Part 4. The facilities -- Part 5. The management functions
Includes index.
Keywords: FOOD SERVICE MANAGEMENT